GOVERNMENTAL SUPPORT MECHANISM OF THE RENEWABLE ENERGY IN GERMANY - N. V. Kozaeva (MGIMO University Press, 2016)
German Energy transition could be considered to be one of the most challenging a widescaled reforms, quite capital-intensive, requiring a high level of scientific input, having an influence on other economic sectors and economic entities. Energy reform is intended to increase the energy security level by increasing the share of renewables in its energy portfolio, environmental protection by decreasing the emission into the atmosphere and the level of energy consumption. Since 1990 the share of renewables in the whole energy sector and in electricity sector has been rising steadily. Governmental support, including direct finance, fiscal benefits and creating favorable market conditions for the sector has been expanding for renewable and declining for traditional energy. The costs for renewable energy are more transparent, during those for traditional energy are often hidden and indirectly charge the budget, can emerge later in form of subsequent costs of the climate. However, the system of support itself discloses its imperfection, when its implementation causes an opposite impact or contradiction between several instruments, which are actually aimed to solve one problem. Given the high strategic importance of the goals set, even an evident necessity to revise the mechanism of governmental support doesn't, however, mean that the government doubts the usefulness of the reform.